Big Data and Libraries: Identifying Themes in the Literature. Issue 1 (3rd April 2018) - Blummer, Barbara; Kenton, Jeffrey M.
Abstract: The availability of big data is increasing in various sectors of the economy worldwide. Consequently, opportunities for data services are expanding in special, academic and public libraries. Librarians' cataloging, archiving, research, and reference skills remain especially suited for the provision of big data services. In this article the authors examine the literature on big data and libraries to identify major themes as well as highlight possibilities and problems with the management of large datasets. Librarians can utilize this information to develop or improve data services in their institutions' libraries.